Challenges and opportunities in free-standing supercapacitors research - Latham,KG; Edathil,AA; Rezaei,B; Liu,S; Nguyen,S; Keller,SS; Torrisi,F; Greenhalgh,ES; Titirici,M-M (APL Materials, 2022)
The design of commercial supercapacitors has remained largely unchanged since the 1970s, comprising powdered electrodes housed in rigid metal cylinders or pouches. To power the next generation of integrated technologies, an evolution in supercapacitor materials and design is needed to create multifunctional materials that allow energy storage while imparting additional material properties (e.g., flexibility and strength). Conductive free-standing electrodes produced from fibers or 3D printed materials offer this opportunity as their intrinsic mechanical properties can be transferred to the supercapacitor. Additionally, their conductive nature allows for the removal of binders, conductive agents, and current collectors from the supercapacitor devices, lowering their economic and environmental cost. In this Perspective, we summarize the recent progress on free-standing supercapacitors from new methods to create free-standing electrodes to novel applications for these devices, together with a detailed discussion and analysis on their electrochemical performance and physicochemical and mechanical properties. Furthermore, the potential directions and prospects of future research in developing free-standing supercapacitors are proposed.